Appeals to Interest Language, Contestation, and the Shaping of Political Agency. - Mathiowetz, Dean (Penn State University Press, 2015)
It has become a commonplace assumption in modern political debate that white and rural working- and middle-class citizens in the United States who have been rallied by Republicans in the "culture wars" to vote Republican have been voting "against their interests." But what, exactly, are these "interests" that these voters are supposed to have been voting against? It reveals a lot about the role of the notion of interest in political debate today to realize that these "interests" are taken for granted to be the narrowly self-regarding, primarily economic "interests" of the individual. Exposing and contesting this view of interests, Dean Mathiowetz finds in the language of interest an already potent critique of neoliberal political, theoretical, and methodological imperatives--and shows how such a critique has long been active in the term's rich history. Through an innovative historical investigation of the language of interest, Mathiowetz shows that appeals to interest are always politically contestable claims about "who" somebody is--and a provocation to action on behalf of that "who." Appeals to Interest exposes the theoretical and political costs of our widespread denial of this crucial role of interest-talk in the constitution of political identity, in political theory and social science alike.